Cost-effectiveness analysis of first-line tislelizumab plus chemotherapy for extensive-stage small cell lung cancer from the perspective of the healthcare system in China - Chen, Feng; Feng, Xue; Xiao, Lin Lin; Tang, Hai Juan; Qin, Shu Xia; Peng, Jie Ping; Bai, Jing (Frontiers in Public Health, 2025)
BackgroundExtensive-stage small-cell lung cancer (ES-SCLC) poses a formidable challenge due to its aggressive nature and poor prognosis. While immune checkpoint inhibitors have shown promise as part of first-line therapy, their cost-effectiveness and survival benefits in the Chinese healthcare system are not well understood. This study evaluates the cost-effectiveness of first-line tislelizumab combined with chemotherapy versus chemotherapy alone for ES-SCLC.MethodsWe conducted a cost-effectiveness analysis using a partitioned survival mode (PSM) to compare tislelizumab plus chemotherapy versus chemotherapy alone for the first-line treatment of ES-SCLC. The model integrated survival estimates from the RATIONALE-312 Phase III clinical trial, direct medical costs, and quality-adjusted life year (QALY) sourced from the literature. We calculated 10-year cost per QALY gained from Chinese healthcare system perspective. The analysis of cost-effectiveness was benchmarked against a willingness-to-pay threshold three times of GDP per capita in China. Sensitivity analyses were conducted to evaluate parametric uncertainty and model robustness.ResultsCompared to the chemotherapy alone group, the tislelizumab plus chemotherapy group resulted in an incremental cost-effectiveness ratio (ICER) of US31,072.79 per quality-adjusted life-year (QALY), which is below the threshold of US37,765 per QALY. Sensitivity analyses indicated that the utility value of progression-free survival (PFS) is a principal determinant of the ICER, with the ratio fluctuating between 27,246 and 36,417 per QALY, well below the willingness-to-pay threshold. In scenario analyses, tislelizumab plus chemotherapy resulted in an ICER of US 38,665.59/QALY with PET-CT imaging (exceeding the 37,765/QALY threshold) but was cost-effective at US 30,076.37/QALY when imported topotecan was used as second-line treatment.ConclusionTislelizumab plus chemotherapy demonstrates cost-effectiveness in the first-line treatment of ES-SCLC in China. This study provides preliminary evidence for the economic value of tislelizumab in the treatment of ES-SCLC, supporting its consideration as a first-line therapeutic option.